2012
DOI: 10.5539/cco.v1n2p109
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Properties of Hydroxycinnamic Acids -A Review

Abstract: Hydroxycinnamic acid compounds are an important source of antioxidants due to their ubiquitous occurrence in the plant kingdom and their characteristic activities. Due to their antioxidant activity, several researchers have attributed a probable role of these compounds in the prevention of various diseases associated with oxidative stress, such as cancer and cardiovascular diseases. Recent evidence suggests that these compounds may also act by other mechanisms in addition to the antioxidant capacity as modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 62 publications
1
77
1
1
Order By: Relevance
“…In our study, a correlation between a high content of p-hydroxybenzoic and a low content of syringic acids occurred only in the case of Spanish 'Morado' cultivar. The hydroxybenzoic acid derivatives, especially p-hydroxybenzoic acid, have been consistently associated with a reduced risk of cardiovascular diseases, cancer and other chronic diseases [Rocha et al, 2012;Spencer et al, 2008]. In our study, we did not detect the epicatechin fl avonoid in extracts from Polish 'Harnaś', Spanish 'Morado', Chinese and Portuguese garlic cultivars.…”
Section: Discussioncontrasting
confidence: 76%
“…In our study, a correlation between a high content of p-hydroxybenzoic and a low content of syringic acids occurred only in the case of Spanish 'Morado' cultivar. The hydroxybenzoic acid derivatives, especially p-hydroxybenzoic acid, have been consistently associated with a reduced risk of cardiovascular diseases, cancer and other chronic diseases [Rocha et al, 2012;Spencer et al, 2008]. In our study, we did not detect the epicatechin fl avonoid in extracts from Polish 'Harnaś', Spanish 'Morado', Chinese and Portuguese garlic cultivars.…”
Section: Discussioncontrasting
confidence: 76%
“…It is indicated that caffeic acid esters prevent metastasis of tumor cells into lung. In addition, caffeic acid-rich Prunella (Apiaceae) extracts are effective in prevention and treatment of lung cancer [25]. Another group found in subfractions is benzoic acid derivatives.…”
Section: Lc/ms-ms Resultsmentioning
confidence: 99%
“…There is an increasing number of studies indicating that hydroxycinnamic acids prevent invasion and metastasis of cancer cells. As shown in various sources, caffeic acid and their esters, pcoumaric acid, ferulic acid showed anticancer effects against cancer cells such as column, lung, breast, liver, prostate, cervix and gastric [25][26][27][28][29]. It has been determined that p-coumaric acid, ferulic acid and caffeic acid significantly reduce survival rate of MDA-MB 468 and HBL 100 breast cancer cells, also colony formations of MDA-MB 468 cells.…”
Section: Lc/ms-ms Resultsmentioning
confidence: 99%
“…Phenolic compounds are secondary metabolites of plants widely distributed in foods of plant origin. They are involved in defence against ultraviolet radiation or aggression by pathogens (Manach et al 2004;Rocha et al 2012). Phenolic acids are the most widespread phenolic compounds in grains, and settle in crusts of piece such as mostly pericarp, testa, and aleurone (Kandil et al 2012).…”
mentioning
confidence: 99%